Investigation Influence of Channel Transport on Output Characteristics in Sub-100nm Heterojunction Tunnel FET - Yunhe Guan; Haifeng Chen; Siwei Huang; Feng Liang (IEEE Journal of the Electron Devices Society, 2021)
In this paper, the influences of channel transport on the output characteristic in sub-100nm heterojunction tunnel FET have been investigated through TCAD simulation. The calibrated tunneling and transport parameters with experiment have been adopted. The influences of the parameters characterizing channel transport, i.e., mobility, channel length, and saturation velocity, are analyzed in detail under different biases. It is found that the channel transport has stronger impact on the performance of the device biased in the linear region and with smaller mobility, longer channel, and higher saturation velocity. The saturation drain voltage can be reduced by improving the mobility and reducing the saturation velocity. However, the latter will reduce the current simultaneously. What’s more, considering quantum confinement, the variation in performance of the device induced by the change of mobility is still visible after some optimization strategies are used.